An economic analysis of the service area scheme - Serafica, Ramonette B. (1997)
Under the service are scheme, firms are required to install basic telephone service as a condition to compete in the cellular and international phone service markets. This study looks at the case of Metro Manila which was arbitrarily subdivided by the regulator into four sections as part of the scheme. Using a process model, the cost of providing basic telephone service in each section is determined for different output levels corresponding to market shares likely to be captured by a new firm. The cost data provided by the process model are then used as input for the econometric analysis where a translog cost function is estimated.
Includes bibliographical references (pages 95-98).
Keywords: Telecommunication; Telephone